Pedagogical Model of Organization of Distance Teaching and Learning in the Conditions of Network Technology of Students’ Educational and Creative Activity Management - Nahaev, Viktor; Hrynova, Yana (Educational Challenges, 2020)
Theoretical and methodical bases of management concepts, information and digital technologies implementation into the educational environment in the conditions of distance teaching and learning are analyzed. The purpose of the paper is to develop a comprehensive pedagogical model of distance teaching and learning organization in the conditions of implementation of network technology of students’ educational and creative activity management. The research methodology was determined by a set of methodological approaches (systemic, activity, competence, personality-developing) and was based on a pedagogical experiment which included ascertaining, forming and control stages. The results are as follows: it is well-proven that the only Internet platform for creation of educational SMART-environment in the higher education institution should be basic for organization of distance teaching and learning. It allows automation of teaching and learning processes, which is provided for a network contact of students and teachers in the interactive mode. Pedagogical model of distance teaching and learning organization in the conditions of network technology of student’s educational and creative activity management is offered. It consists of the pedagogical system components, diagnostic SMART-complex and methods of pedagogical influence. Technological stages and content of distance teaching and learning organization are justified in educational SMART-environment. Methods, forms and facilities of realization of the studied phenomenon are substantiated in the system of didactics educational complexes. It has been defined that the basic link of distance teaching and learning organization is a telecommunication environment, which includes: informatively-digital, educational-methodical and didactics contents. Experimental work performances have proved the substantial increase of high-quality indexes of the agrarian sphere students’ professional training (success, motivation, creative activity, productivity) in the conditions of implementation of network technology of students’ educational and creative activity management. The conclusion is that the realization of this pedagogical model in the system of distance teaching and learning allows to intensify considerably students’ creative activity, to promote a level of their internal motivation, to deepen the level of independence and individualization of studies, that in a result is determined by the high level of future specialists’ professionally-creative competence development.